PERTUMBUHAN, HISTOPATOLOGI OVARIUM DAN FEKUNDITAS IKAN NILA MERAH (OREOCHROMIS NILOTICUS) SETELAH PAPARAN PESTISIDA ORGANOFOSFAT - SETYAWATI , IRIANI; WIRATMINI, NGURAH INTAN; WIRYATNO, JOKO (Jurnal Biologi Udayana; Vol 15 No 2 (2011): Jurnal Biologi, 2011)
Fish cultures in rice fields or areas that use water from a pesticide-polluted irrigation or river, are particularly vulnerable to the negative impact of pesticides. This study aims to assess the effect of organophosphates on growth, ovarian histopathology and fecundity of red tilapia (Oreochromis niloticus). After acclimatization, 160 fishes (fingerlink stage) were kept in four ponds sized 2x1,5x0,8 m each. This study used a complete randomized block design and organophosphate administration through the feed. The study used four groups: control, and variations in dose of 2 ml (D1), 6 ml (D2), and 10 ml (D3) of pesticide per 100 grams of pellet, which is given in the morning (treatment) and in the evening (regular feed). Data were taken at week 3, 6, and 9, then the organophosphate treatments were stopped, and the last data were taken at week-18. Statistical analysis was performed by Anova and Duncan's Multiple Range Test. The results showed that the organophosphate pesticide inhibits the growth by reducing fish length and weight, reducing ovarian weight, increasing the number of oocyte atresia, damaging structure of the ovarian histology, and decreasing fecundity by reducing the number of egg production in the ovarian of red tilapia.
Keywords: organophosphate; growth; ovarian histology; fecundity